Smoking-induced craving relief relates to increased DLPFC-striatal coupling in nicotine-dependent women. (1st April 2021) - Franklin, Teresa R.; Jagannathan, Kanchana; Spilka, Nathaniel H.; Keyser, Heather; Rao, Hengy; Ely, Alice V.; Janes, Amy C.; Wetherill, Reagan R.
Highlights: Craving is a major contributor to drug-seeking and relapse. Instead of inducing craving, this study reports on relief of craving. Smokers participated in fMRI before and after smoking. Smoking-induced increases in dlPFC-striatal coupling is associated with craving relief. Modulation of the dlPFC is a viable treatment option to reduce craving. Abstract: Background: Craving is a major contributor to drug-seeking and relapse. Although the ventral striatum (VS) is a primary neural correlate of craving, strategies aimed at manipulating VS function have not resulted in efficacious treatments. This incongruity may be because the VS does not influence craving in isolation. Instead, craving is likely mediated by communication between the VS and other neural substrates. Thus, we examined how striatal functional connectivity (FC) with key nodes of networks involved in addiction affects relief of craving, which is an important step in identifying viable treatment targets. Methods: Twenty-four nicotine-dependent non-abstinent women completed two resting-state (rs) fMRI scans, one before and one following smoking a cigarette in the scanner, and provided craving ratings before and after smoking the cigarette. A seed-based approach was used to examine rsFC between the VS, putamen and germane craving-related brain regions; the dorsolateral prefrontal cortex (dlPFC), the posterior cingulate cortex, and the anterior ventral insula. Results: Smoking a cigarette was associated with a decrease in craving. Relief of craving correlated with increases in right dlPFC- bilateral VS (r = 0.57, p = 0.003, corrected) as did increased right dlPFC-left putamen coupling (r = 0.62, p = 0.001, corrected). Conclusions: Smoking-induced relief of craving is associated with enhanced rsFC between the dlPFC, a region that plays a pivotal role in decision making, and the striatum, the neural structure underlying motivated behavior. These findings are highly consistent with a burgeoning literature implicating dlPFC-striatal interactions as a neurobiological substrate of craving.